Energy Absorption Performance Of Natural Fibres Reinforced Epoxy Composite Tubes Under Axial And Oblique Loading - Lau, Saijod Tse Way (2021)
For the current study, kenaf fibre and jute fibre has been used to reinforced epoxy thermoset to become structural tubes as safety device in vehicle which made of natural fibre reinforced epoxy composites. Automobiles nowadays are using metal crash cans. However these crash cans have put more weight for the vehicles and the performance of the metal cans is compromised. Therefore in this work, there are three main parts of studies. Firstly, it is the suitable types of fibre and its orientation reinforced in epoxy for structural crashworthiness. Then, the suitable type of orientation is chosen to study the effect of triggering onto the structural designs. Lastly, the experience and their failure analysis will help to design for the prototype application as crash can in vehicle. In first part, kenaf fibre with random orientation and unidirectional orientation reinforced with epoxy were prepared into composites square hollow section (SHS) and tested against neat epoxy. Secondly, effect of triggering is done using two types of fibres namely jute and kenaf fibres and both were reinforced with epoxy. Both composite were formed in SHS and round tubes and triggering effect such as tulip type, 450 single chamfer and double chamfer were compared. Last but not least, preparation of the prototype samples for Proton were prepared using SHS, cylindrical and tapered structure. All the tests were undergoes quasi-static axial crushing of 10 mm/min. Their peak load (Pmax), mean load (Pmean), energy absorption (EA) and specific energy absorption (SEA) have been recorded. In the study of types of fibre and its orientation, kenaf fibre reinforced epoxy (KFRE) has been made into square hollow section (SHS). It is found that unidirectional fibre orientation (U-KFRE) gives the best energy absorption compared to unreinforced epoxy (neat epoxy, NE) and random kenaf fibre reinforced epoxy (R-KFRE). Both the specimens (NE and R-KFRE) failed catastrophically. For the triggering effect, circular tubes and SHS made of jute fibre reinforced epoxy (JFRE) composites have been fabricated. The two cross sectional tubes were introduced with triggering types namely, tulip type, 450 single chamfer and double chamfer. From the test, it is found that, tulip type chamfered give the best energy absorption (EA) and specific energy absorption (SEA). The SEA for the tulip triggered circular and SHS JFRE are 33.17 kJ/kg and 31.29 kJ/kg, respectively. From the results, three prototypes namely, square box, cylinder and taper cylinder structure were made based on Proton Prevé crash can. The prototypes performance were compared with existing product which taper cylinder recorded weight reduction and SEA of 59 % and 190 %, respectively